1994
DOI: 10.1099/00207713-44-2-362
|View full text |Cite
|
Sign up to set email alerts
|

A New Serovar in the Grippotyphosa Serogroup Comprising Leptospiral Isolates from Different Regions

Abstract: Pulsed-field gel electrophoresis (PFGE) studies performed with leptospiral isolates led us to suspect the existence of a new serovar in the Grippotyphosa serogroup. The results obtained with reference serological techniques used in leptospiral identification, including cross-agglutination absorption and monoclonal antibody techniques, confirmed the existence of a new serovar exemplified by strain Dadas I. Four other isolates from different regions of the world were submitted for identification by PFGE and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…1987). Although CAAT results indicated Dadas to be a new serovar, also in this case moderate to low residual titres in the reversed reactions of CAAT were found (Hermann et al, 1994). Apparently, CAAT is not suitable anymore to differentiate several serovars currently placed into serogroup Grippotyphosa.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…1987). Although CAAT results indicated Dadas to be a new serovar, also in this case moderate to low residual titres in the reversed reactions of CAAT were found (Hermann et al, 1994). Apparently, CAAT is not suitable anymore to differentiate several serovars currently placed into serogroup Grippotyphosa.…”
Section: Discussionmentioning
confidence: 82%
“…It was not possible to distinguish with both the mAb and PCR analysis between serovars Dadas and Ratnapura. However, Dadas has been isolated from mammals in Turkey, Israel and Russia (Hermann et al, 1994), while Ratnapura is exclusively 112 R. A. Hartskeerl et al found in Southeast Asia (Kmety and Dikken, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Genomic macrorestriction with Not I followed by PFGE is considered to be a powerful typing method for classifying Leptospira strains at the serovar level [29], [30], [31], [43]. For example, classification of the Dadas I strain as a new serovar of serogroup Grippotyphosa was strongly supported by its unique pulsed-field gel electrophoresis pattern [43].…”
Section: Discussionmentioning
confidence: 99%
“…For example, classification of the Dadas I strain as a new serovar of serogroup Grippotyphosa was strongly supported by its unique pulsed-field gel electrophoresis pattern [43]. The clinical isolates from Mayotte had PFGE patterns that were different to those for the reference strains belonging to serogroups Mini, Hebdomadis, Pyrogenes, and Grippotyphosa (Text S1).…”
Section: Discussionmentioning
confidence: 99%
“…Antisera. Purified murine monoclonal antibody F71C2 (22 mg/ml), specific for grippotyphosa serovars, has been described previously (25). Reactivity of monoclonal antibody F71C2 with the LPS antigen of L. kirschneri, serovar grippotyphosa strain RM52, has been demonstrated by immunoblotting (23).…”
mentioning
confidence: 99%